Controlling the nanomorphology of thin conformal Cu2S overlayers grown on Cu2O compact layers and nanowires - Minguez-Bacho, Ignacio; Courte, Marc; Shi, Chen; Fichou, Denis (Materials Letters, 2015)
Thin conformal Cu2S overlayers are grown on Cu2O compact layers (CLs) and nanowires (NWs) by ion exchange reaction (IER). This method is based on the exchange of O2- into S2- ions at the surface of Cu2O in a solution-containing Na2S acting as the sulfur ions source. The Cu2S overlayers are grown under different experimental conditions by varying the Na2S concentration and the duration of the IER process, thus leading to different Cu2S nanomorphologies. In particular, when a concentration of 2 mM Na2S is used, hexagonal Cu2S nanocrystals are formed on the surface of both Cu2O CLs and NWs. These nanocrystals are of larger size at the ridges of the Cu2O cubes in CLs and at the tips of Cu2O in NWs. The high-quality crystal structure and composition of Cu2S are confirmed by high resolution transmission electron spectroscopy and X-ray photoluminescence spectroscopy. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ion exchange reaction; Nanomorphology; Overlayer; Copper oxide; Copper sulfide